2021
DOI: 10.1038/s41467-021-26854-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stages of evolutionary change in anthrax toxin receptor expression in humans

Abstract: The advent of animal husbandry and hunting increased human exposure to zoonotic pathogens. To understand how a zoonotic disease may have influenced human evolution, we study changes in human expression of anthrax toxin receptor 2 (ANTXR2), which encodes a cell surface protein necessary for Bacillus anthracis virulence toxins to cause anthrax disease. In immune cells, ANTXR2 is 8-fold down-regulated in all available human samples compared to non-human primates, indicating regulatory changes early in the evoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Despite the effectiveness of modern vaccines, scientists are searching for the development of the most areactogenic preparations, namely the improvement of anthrax vaccines to reduce irritation and inflammation at the injection site. Similar reactions occur in case of an edematous and lethal factor [29][30][31]. Another important criterion is an increase in the duration of immunity, an increase in the production of protective antigen by vaccine producing strains.…”
Section: Literature Reviewmentioning
confidence: 80%
See 2 more Smart Citations
“…Despite the effectiveness of modern vaccines, scientists are searching for the development of the most areactogenic preparations, namely the improvement of anthrax vaccines to reduce irritation and inflammation at the injection site. Similar reactions occur in case of an edematous and lethal factor [29][30][31]. Another important criterion is an increase in the duration of immunity, an increase in the production of protective antigen by vaccine producing strains.…”
Section: Literature Reviewmentioning
confidence: 80%
“…The BioThrax vaccine in the US (formerly known as AVA) and the similar AVP vaccine in the UK are alum-adsorbed culture filtrates of vaccine strains of the anthrax pathogen that contain PA. Earlier studies have shown that exotoxin immunization of various animal models provides protection against anthrax infection [29][30][31]. A post-vaccination correlation of PA antibody titres has also been established [32; 33].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar evolution of these genes in apes has not occurred, nor has there been recent evolution of these genes in humans (Moon et al, 2018), suggesting that the selection pressure was increased carnivory‐rated spillover c. 2 mya (Khan et al, 2020). There is also evidence that resistance to Bacillus anthracis , a zoonotic bacterium that spills over from ruminants into humans, evolved early in modern human evolution (Choate et al, 2021). Finally, unlike chimpanzees and other vertebrates, humans have three high frequency apolipoprotein E alleles, which are linked to meat‐eating and improved immune defense, among other things (Finch & Stanford, 2004; Vitek et al, 2009; cf.…”
Section: Physiological and Genetic Evidence For Human‐specific Immune...mentioning
confidence: 99%
“…Transcriptional regulation, the mechanism by which cells dynamically modulate the expression of each gene in their genome, plays a pivotal role in nearly every cellular process and is among the most important molecular pathways underlying variation in complex traits [1][2][3][4][5][6][7][8][9]. Transcription is controlled by at least two classes of transcription factor protein, which bind to characteristic DNA sequence motifs and work in concert to tune the rates of early steps during the RNA polymerase II (Pol II) transcription cycle [10].…”
Section: Introductionmentioning
confidence: 99%